Hospital food management: a multi-objective approach to reduce waste and costs - Arriz-Jorquiera, Mariana; Acuna, Jorge A.; Rodríguez-Carbó, Marian; Zayas-Castro, José L. (Waste management (Elmsford), 2024)
•The MIP bi-objective model can reduce food waste by 19.70 % and cost by 32.66 %.•On average, children waste 35.43 % of their meals, and eat 41.32 g less than adults.•The pediatric ward has the most food waste per meal, leading to a 20 % reduction.•The vegetarian diet exhibits the highest food waste and meal-building cost.•In areas of greatest waste and cost, the models achieved the greatest improvements. Food waste contributes significantly to greenhouse emissions and represents a substantial portion of overall waste within hospital facilities. Furthermore, uneaten food leads to a diminished nutritional intake for patients, that typically are vulnerable and ill. Therefore, this study developed mathematical models for constructing patient meals in a 1000-bed hospital located in Florida. The objective is to minimize food waste and meal-building costs while ensuring that the prepared meals meet the required nutrients and caloric content for patients. To accomplish these objectives, four mixed-integer programming models were employed, incorporating binary and continuous variables. The first model establishes a baseline for how the system currently works. This model generates the meals without minimizing waste or cost. The second model minimizes food waste, reducing waste up to 22.53 % compared to the baseline. The third model focuses on minimizing meal-building costs and achieves a substantial reduction of 37 %. Finally, a multi-objective optimization model was employed to simultaneously reduce both food waste and cost, resulting in reductions of 19.70 % in food waste and 32.66 % in meal-building costs. The results demonstrate the effectiveness of multi-objective optimization in reducing waste and costs within large-scale food service operations.